Genetic diversity of Sterculia quadrifida from Kupang based on ISSR profiles, stomatal density, and chlorophyll content (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Jannah N, Pharmawati M, Uslan. 2022. Genetic diversity of Sterculia quadrifida from Kupang based on ISSR profiles, stomatal density, and chlorophyll content. Biodiversitas 23: 2690-2698. This study investigated the genetic diversity of Sterculia quadrifida R.Br.or faloak based on Inter Simple Sequence Repeats (ISSR) molecular markers and determined stomatal density and chlorophyll content from several localities in Kupang District, East Nusa Tenggara, Indonesia. For genetic diversity analysis, samples were collected from the Oelsonbai forest area of Maulafa Sub-district, Kupang City, whereas for stomatal density and chlorophyll content analysis, samples were collected from areas with various degrees of anthropogenic activity from Kupang city. DNA was isolated using Cetyl Trimethyl Ammonium Bromide (CTAB) method and amplified by three ISSR primers (UBC 811, UBC 812, and UBC 815), whereas stomatal density was observed using a microscope and chlorophyll content was determined using a spectrophotometer. Genetic data were analyzed using the unweighted pair group method with arithmetic mean (UPGMA) method and Nei & Li coefficient similarity in the MVSP software. A total of 78 ISSR bands ranging from 320-3200 bp were obtained, where populations were divided into four main clusters and six sub-clusters, similarly having moderate heterozygosity (He=0.50) not clustered based on their geographical distribution. There was a difference in stomatal density and chlorophyll content, probably influenced by anthropogenic disturbances. A conservation action plan is required to ensure the S. quadrifida's survival in the future.